1984
DOI: 10.1084/jem.160.4.1012
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory mechanisms in immune responses to heterologous insulins. II. Suppressor T cell activation associated with nonresponsiveness in H-2b mice.

Abstract: Murine antibody responses to insulins are controlled by MHC-linked Ir genes. Although mice of the H-2b haplotype do not make antibody in response to pork insulin, we demonstrate in this communication that immunization with pork insulin stimulates radioresistant, Lyt-1+2- helper T cells that are capable of stimulating secondary antibody responses to pork insulin in vitro, but that this activity is masked by radiosensitive, Lyt-1-2+, I-J+ suppressor T cells. The suppressor T cells, present after immunization wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

1986
1986
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 22 publications
1
23
1
Order By: Relevance
“…Moreover, primed mice that were boosted several times with INS failed to develop evidence of pancreatic infiltration beyond the occasional interstitial infiltration of mononuclear cells seen in control mice primed with CFA alone (41). The failure of the INS-CTL to induce diabetes cannot be attributed to the lack of CD4 ϩ helper T cells because they are activated by both BINS and HINS in CFA (1,16,17). It is not clear whether the failure to develop diabetes in B6 mice is due to a precursor frequency that is below the threshold to produce disease, expression of TCR with low avidity, the lack of other essential signals required to target the CTL to the pancreas, the cytokine profile of the INS-CTL, or other factors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, primed mice that were boosted several times with INS failed to develop evidence of pancreatic infiltration beyond the occasional interstitial infiltration of mononuclear cells seen in control mice primed with CFA alone (41). The failure of the INS-CTL to induce diabetes cannot be attributed to the lack of CD4 ϩ helper T cells because they are activated by both BINS and HINS in CFA (1,16,17). It is not clear whether the failure to develop diabetes in B6 mice is due to a precursor frequency that is below the threshold to produce disease, expression of TCR with low avidity, the lack of other essential signals required to target the CTL to the pancreas, the cytokine profile of the INS-CTL, or other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that injection of PINS in CFA stimulated CD8 ϩ T cells that prevent the development of an Ab response in nonresponder B6 mice (1,2). Removal of the CD8 ϩ T cells revealed that radioresistant, CD4 ϩ helper T cells had been primed by PINS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations